2014
DOI: 10.4038/cjsbs.v42i2.6611
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Contents in Muscle Tissues of Inland Fish Species in the North Central Province of Sri Lanka

Abstract: Chronic Kidney Disease (CKD) has recently shown a remarkable increase in some areas in the North Central Province (Anuradhapura and Polonnaruwa districts), Sri Lanka. The consumption of fresh water fish contaminated with trace metals is considered as a possible causal factor for this. The concentration of mercury (Hg), lead (Pb), cadmium (Cd), chromium (Cr), copper (Cu), cobalt (Co), zinc (Zn), iron (Fe) and arsenic (As) in the muscle tissues of the five commonly consumed freshwater fish species, Oreochromis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
3
2
Order By: Relevance
“…According to the Indrajith, Pathiratne [53] the Cd concentration of two fish species, Etroplus suratensis(0.011 -0.027 ppm) and Ambassis commersoni (0.001-0.034 ppm) were detected from 12 sites ofNegombo estuary. The concentrations are exceeding the values of the present study.Jinadasa, Ariyarathne [54] was observed that Cd in inland fish species Orinoco Sailfin Catfish (Pterygoplichthy smultiradiatus) (Male: -0.005 and Female: -0.004 ppm) from two reservoirs Rambakenwewa and Mahaoya) of eastern province Sri Lanka, this values are much closer to present study.Also according to the Jinadasa, Subasinghe [55], the Cd concentration of Oreochromis spp (0.001 ppm) that collected from reservoirs of Anuradhapura and Polonnaruwa districts Sri Lanka, was exceed the value of the present study. Also the value of present study was lower than the value of the Oreochromis spp (0.034 ppm) that was recorded by Jinadasa and Edirisinghe 2012.…”
Section: Hg As CD and Pb In Regurgitated Materialscontrasting
confidence: 77%
See 2 more Smart Citations
“…According to the Indrajith, Pathiratne [53] the Cd concentration of two fish species, Etroplus suratensis(0.011 -0.027 ppm) and Ambassis commersoni (0.001-0.034 ppm) were detected from 12 sites ofNegombo estuary. The concentrations are exceeding the values of the present study.Jinadasa, Ariyarathne [54] was observed that Cd in inland fish species Orinoco Sailfin Catfish (Pterygoplichthy smultiradiatus) (Male: -0.005 and Female: -0.004 ppm) from two reservoirs Rambakenwewa and Mahaoya) of eastern province Sri Lanka, this values are much closer to present study.Also according to the Jinadasa, Subasinghe [55], the Cd concentration of Oreochromis spp (0.001 ppm) that collected from reservoirs of Anuradhapura and Polonnaruwa districts Sri Lanka, was exceed the value of the present study. Also the value of present study was lower than the value of the Oreochromis spp (0.034 ppm) that was recorded by Jinadasa and Edirisinghe 2012.…”
Section: Hg As CD and Pb In Regurgitated Materialscontrasting
confidence: 77%
“…There are many studies of Hg concentration of freshwater fish fauna in Sri Lanka. Jinadasa, Ariyarathne [54] observed that Hg in inland fish species Orinoco Sailfin Catfish (Pterygoplichthy smultiradiatus) (Male: -0.043 and Female: -0.044 ppm) from two reservoirs Rambakenwewa and Mahaoya) of eastern province Sri Lanka, this values are lower than present study.Also according to the Jinadasa, Subasinghe [55], the Hg concentration of Oreochromis spp (0.011 ppm) that collected from reservoirs of Anuradhapura and Polonnaruwa districts Sri Lanka, was not exceed the value of the present study, however it was exceed the value of the Oreochromis spp (0.26 ppm) that was recorded by Jinadasa and Edirisinghe [56].…”
Section: Hg As CD and Pb In Regurgitated Materialscontrasting
confidence: 68%
See 1 more Smart Citation
“…Inland fisheries of the island are mainly practiced in the NCP (Jinadasa et al, 2013). Study by Allinson et al (2009) found that Cadmium (Cd), Copper (Cu), Mercury (Hg), Manganese (Mn), and zinc (Zn) accumulation in Nile tilapia (Oreochromis niloticus L and Oreochromis sp, the most abundance inland fish in Si Lanka), harvested from the freshwater reservoirs such as Kaudulla, Rajanganaya, and Udawalawe reservoirs in Mahaweli, Kala Oya, and Walawe Ganga river basins, respectively.…”
Section: Heavy Metals Contamination and Accumulationmentioning
confidence: 99%
“…However, Allinson et al (2009) further indicated that excess intake of such flesh could lead to health risk to the consumers. Jinadasa et al (2013) highlighted that by consuming contaminated fishes, especially Oreochromis sp. may lead to the incidence of CKDu.…”
Section: Heavy Metals Contamination and Accumulationmentioning
confidence: 99%